Multi Purpose Insurans Bhd : Looking Into The Future - Sabri, Rinorazlin (2004)
Multi Purpose Insurans Bhd (MPIB) is one of the 53 insurance companies in Malaysia. This case was written based on all facts belonging to the company plus other secondary resources. With the vision as its long-term goal, this paper discussed on how MPIB can reach its target via identifying problems, analysis of the current situation and recommendations on further actions.